Evaluation of Supplemental Interactive Learning Material for Teaching Physics in University of the Philippines Los Baños - Pabro, Beverly R.; Dionisio-Sese, Maribel (International Journal on Open and Distance e-Learning, 2019)
With the advent of new technologies being infused in school curricula, educators and school leaders of higher education in the Philippines have embraced e-learning, which involves technology-mediated teaching strategies and a variety of tools to facilitate learning. In this regard, the University of the Philippines Los Baños (UPLB) through the Interactive Learning Center (ILC) started developing and producing online interactive educational materials known as Learning Objects (LOs), which are now being used by UPLB students as supplemental interactive learning materials in various courses in the university. This study focused on the evaluation of the LO on Rotation of Rigid Bodies in terms of knowledge gain of the students and determine its effectiveness in terms of attractiveness, comprehensibility, applicability, interactivity, and assessment function. Students enrolled in PHYS 81 (Fundamental Physics 1) during the First Semester AY 2017-2018 were divided into control and treatment groups and subjected to pre-test-post-test for the LO evaluation. Using the t-test of significance, results showed that the treatment group had a significant increase in the mean scores after being exposed to the LO compared to the control group who did not view the LO, indicating that students aided with LO had greater knowledge gain than those without LO supplementation. Additionally, the Likert scale of scores 1 (strongly disagree) to 5 (strongly agree) was used to evaluate the treatment group’s responses on the different components of the LO. Computing for the weighted mean in each component, results showed that most respondents agreed that the LO was attractive (3.86) and that it was both comprehensible (4.38) and applicable (4.16). Similarly, most respondents in the treatment group agreed that the LO was interactive (4.14) and its assessment items were appropriate (4.28) to the program. Overall, the respondents agreed (4.27) and assessed the evaluated LO as an effective supplementary learning material for the physics topic on the rotation of rigid bodies.